2016
DOI: 10.1002/mus.25047
|View full text |Cite
|
Sign up to set email alerts
|

Cortical hyperexcitability in patients withC9ORF72mutations: Relationship to phenotype

Abstract: Introduction Patients with mutations in C9orf72 can have amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), or ALS-FTD. The goals were to establish whether cortical hyperexcitability occurs in C9orf72 patients with different clinical presentations. Methods Cortical thresholds and silent periods were measured in thenar muscles in 19 participants with C9orf72 expansions and 21 healthy controls using transcranial magnetic stimulation (TMS). El Escorial and Rascovsky criteria were used to diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Additionally, it would be informative to understand the source of intracellular glutamate accumulation; is it due mainly to GGC gene downregulation, to an increase of extracellular glutamate intake, or to a combination of both? Our findings thus provide a possible mechanism to explain the MN hyperexcitability observed specifically in C9 ALS patients (97,98).…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, it would be informative to understand the source of intracellular glutamate accumulation; is it due mainly to GGC gene downregulation, to an increase of extracellular glutamate intake, or to a combination of both? Our findings thus provide a possible mechanism to explain the MN hyperexcitability observed specifically in C9 ALS patients (97,98).…”
Section: Discussionmentioning
confidence: 64%
“…Four of the ALS patients in this study possessed an expansion of the C9ORF72 gene, which has been linked to the presence of electrophysiological brain abnormalities, including cortical hyperexcitability 13 , 14 , background rhythm slowing 15 , and epileptic activity 16 . While there was both a reduction in VEP quality and online BCI performance in ALS patients as a group, those with the C9ORF72 expansion demonstrated further reductions compared to those without it.…”
Section: Discussionmentioning
confidence: 96%
“…MRI studies point to structural changes common among repeat carriers that extend beyond the degeneration of the cortico-motor pathways typically involved in ALS 7 , 11 , 12 . Transcranial magnetic stimulation studies have identified a reduction in cortical inhibition attributable to this expansion found in ALS patients 13 , 14 . In an electroencephalographic (EEG) study of seven ALS/FTD patients with the repeat expansion, two showed generalized slowing of the background activity, while another two showed intermittent abnormal temporal delta-theta activity 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging clinical functional data for symptomatic ALS patients that carry the C9ORF72 RE shows axonal hyperexcitability in lower motor neurons and the cortex . In direct contrast, cortical hyperexcitability has not been observed in FTD and ALS‐FTD patients, or asymptomatic patients, carrying C9ORF72 RE s .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence for neuronal hyperexcitability has been broadly observed across the genetic spectrum of ALS and has been suggested to manifest pre‐symptomatically before potentially contributing to the degenerative process . Emerging clinical functional data for symptomatic ALS patients that carry the C9ORF72 RE shows axonal hyperexcitability in lower motor neurons and the cortex . In direct contrast, cortical hyperexcitability has not been observed in FTD and ALS‐FTD patients, or asymptomatic patients, carrying C9ORF72 RE s .…”
Section: Introductionmentioning
confidence: 99%